Bioalcohol production from gracilaria sp. fermentation using sasad - Helvie Mansuit (2018)
Marine biomass or macroalgae has been denoted as a potential feedstock due to its high carbohydrate content which can be a source for biofuel production through fermentation process. In this research, Graci/aria sp. from red macroalgae group was used as raw material to produce biofuel via fermentation process. The carbohydrate content in Graci/aria sp. can be breakdown into simple sugar through hydrolysis process such as acid hydrolysis which was reported to be the most affordable and available method to be done. This process, however, may release inhibitors such as furfural and 5 HMF (hydroxymethyl furfural). Nonetheless, common ethanol producing agent such as Saccharomyces cerevisiae was reported unable to undergo a succesfully alcohol metabolic pathway in any substrate containing inhibitors. Thus, in this research Graci/aria sp .. was fermented using a local Borneo bioagent, Sasad. The effect of acid concentration variation from 0.2 M to 0.8 M in acid hydrolysis on glucose content and alcohol yield of Graci/aria sp. was described. Acid concentration of more than 0.8 M was not explored as it higher acid concentration of more than 1 M was believed to yield higher inhibitors such as levulinic acid that was formed from HMF. Then, the effect of acid hydrolysis duration ranging from 15 to 60 minutes on glucose content and alcohol yield was also measured. The alcohol content of Graci/aria sp. fermentation product was also analysed based on the effect of fermentation duration and pretreatment types. The highest glucose content before fermentation process was recorded from Graci/aria sp. hydrolyzed using 0.8 M sulphuric acid for 30 minutes yielded 18.25 g/L compared to unhydrolyzed and hot water treated Gracilariasp., 13.34 g/L and 14.22 g/L respectively. After fermentation, lowest glucose content showed by untreated Graci/aria sp. after 7 days fermentation; with only 7.57 g/L glucose left. Alcohol content analysis using GCMS showed that 1 - butanol - 3 - methyl or isoamyl can be detected in all fermentation product. Highest alcohol yield was obtained from untreated Graci/aria sp. after 28 days fermentation which was 0.486x1Q-4 g/g followed by hot water treated and acid hydrolyzed samples of 0.121x1Q-4 g/g and 0.030x10-4 g/g respectively. This study has showed that Sasad was able to ferment Graci/aria sp. under different hydrolysis type and it maybe possible to eliminate the pretreatment stage since highest alcohol yield was reported from the untreated sample.